The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s0006-87052009000400018
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento do açaizeiro de terra firme, cultivar pará, sob atenuação da radiação solar em fase de viveiro

Abstract: RESUMOPara avaliar, na Região Noroeste do Estado de São Paulo, o desenvolvimento em fase de viveiro do açaizeiro da cultivar de terra firme Pará, foram monitoradas as respostas do crescimento e da taxa fotossintética, quando submetido a tratamentos de atenuação de 16% e 50% da radiação solar global, até a idade de 8 meses. A altura da planta e o diâmetro do caule, assim como a acumulação de matéria seca, não foram influenciados pelos tratamentos (p< 0,05). Porém, em plantas crescendo sob baixa atenuação de irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 11 publications
(5 reference statements)
4
13
0
Order By: Relevance
“…In an environment with low luminosity the açaizeiro shows good development and the physiological and morphological responses will depend on the levels of radiation they are exposed (GAMA et al, 2003). Conforto and Contin (2009) confirmed these observations when they found that E. oleracea had a better development with 50% of shading compared to full sunlight. These authors observed an improvement of leaf area expansion, which maximized the interception of clarity and light use more efficiently, leading to increase in carbon gain in low solar irradiations.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…In an environment with low luminosity the açaizeiro shows good development and the physiological and morphological responses will depend on the levels of radiation they are exposed (GAMA et al, 2003). Conforto and Contin (2009) confirmed these observations when they found that E. oleracea had a better development with 50% of shading compared to full sunlight. These authors observed an improvement of leaf area expansion, which maximized the interception of clarity and light use more efficiently, leading to increase in carbon gain in low solar irradiations.…”
Section: Resultsmentioning
confidence: 68%
“…In açaizeiros grown in Amapa, Conforto and Contin (2009) found 2.32 g for the root and 6.79 g for the aerial part in plants of the same age. Such values are also very close to those found by Bovi et al (1994) for E. oleraceae grown in Campinas (SP), where the dry matter weight ranged from 2 to 10 g for the set of stem and leaves and between 0.4 and 2.4 g for the root.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…However, part of the açaí fruit production comes from commercial plantations usually installed in upland areas, without the use of irrigation, thus depending exclusively on rainfall, or with the use of empirically managed irrigation (Homma et al, 2006). Such scenario tends to change over time, due to the development of new management techniques and employment of plant materials more adapted to upland areas, such as the cultivar BRS-Pará (Conforto & Contin, 2009;Oliveira & Farias Neto, 2004) and the ecotype Hideo.…”
Section: Introductionmentioning
confidence: 99%
“…The açaí palm, which is native to the Brazilian Amazon (Conforto and Contin ), is an allogamous, perennial palm propagated almost exclusively by seed (Neto and Oliveira ), resulting in high genetic variability (Neto et al . ).…”
Section: Introductionmentioning
confidence: 99%